Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.22146/bkm.12563
|View full text |Cite
|
Sign up to set email alerts
|

Dukungan sosial dan kualitas hidup orang dengan HIV/AIDS

Abstract: Purpose: This study aimed to determine the quality of life among people living with HIV/AIDS based on the criteria for diagnosis and other factors.Methods: This study was conducted in the VCT clinic hospital of Dr. Moewardi. The population was HIV-positive patients with antiretroviral therapy. Data collection conducted through medical records and interview to patients. Results: Out of a total of 89 respondents, 66.29% were males and 71.91% were aged between 26-45 years. We found significant correlations for di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Fadillah & Eryani (2019) mengungkapkan bahwa keyakinan diri dalam menjalankan tugas berperan penting. Menurut Primardi & Hadjam (2011) keyakinan diri ini akan membentuk pandangan positif terhadap masa depan yang akan berakhir baik terlepas dari segala masalah yang sedang dihadapi dan kemungkinan masalah yang akan terjadi disebut optimisme lalu akan terbentuk dan terwujud pada perilaku.…”
Section: Pendahuluanunclassified
“…Fadillah & Eryani (2019) mengungkapkan bahwa keyakinan diri dalam menjalankan tugas berperan penting. Menurut Primardi & Hadjam (2011) keyakinan diri ini akan membentuk pandangan positif terhadap masa depan yang akan berakhir baik terlepas dari segala masalah yang sedang dihadapi dan kemungkinan masalah yang akan terjadi disebut optimisme lalu akan terbentuk dan terwujud pada perilaku.…”
Section: Pendahuluanunclassified
“…PLWHA who have received a social support had an opportunity to evaluate a good quality of life as much as 10.81 times compared with those who do not receive social support. Mardia et al (2017), suggested that factors affecting the quality of life such as length of diagnosis, ARV therapy, sex, transportation, age, diagnostic criteria and social support. Social support will minimize psychosocial pressure on people living with HIV, so people living with HIV have a better lifestyle and can respond more positively to their social environment (Sarafino, 2011).…”
Section: The Effect Of Healthy Behavior and Quality Of Lifementioning
confidence: 99%
“…Kerentanan wanita berakar kuat pada ketidaksetaraan gender yang membatasi mobilitas mereka, membuat mereka kurang mampu melepaskan diri dari bahaya dan melindungi diri dari konsekuensi bencana yang dialaminya (Bizzarri, 2012). Kerentanan tersebut juga berkaitan erat dengan optimisme dan harapan untuk bangkit kembali dari masalah (Primardi & Hadjam, 2011). Selain itu, mereka memiliki strategi koping yang rendah dalam situasi bencana.…”
Section: Pendahuluanunclassified